Influence of epitaxial BiFeO3 on superparamagnetic behavior of CoFeB thin film - Zhang, Q. T. (2015)
Superparamagnetic behavior of ultrathin CoFeB film grown on epitaxial BiFeO3 (BFO) thin film was investigated by using anomalous Hall effect (AHE) at different temperatures. A transition from superparamagnetism to blocked state was observed for CoFeB grown directly on SrTiO3 (STO) substrate, but absent for CoFeB grown on BFO from 30 K to 300 K. By fitting normalized AHE data with Langevin equation, average grain sizes of the superparamagnetic CoFeB grown on STO and BFO were estimated. Considering the relationship between volume of nanoparticle and blocking temperature ( TB ), TB of CoFeB grown on BFO was above 30 K which was not observed experimentally, indicating that in addition to surface roughness or oxidation, interfacial exchange coupling also played a role in the suppression of TB . By taking the interfacial exchange coupling between BFO and superparamagnetic CoFeB as an effective field, Bloch equations were introduced to study the relaxation process of superparamagnetic CoFeB. This suppression of TB was proposed to be attributed to a cooperative effect of interfacial exchange coupling as well as roughness or oxidation between BFO and superparamagnetic CoFeB.